Voter Data Management Application for Legislative Candidate - Rijois I. E. Saragih (International Journal of Information System and Innovative Technology, 2023)
This research introduces a cutting-edge "Voter Data Management Application" tailored for legislative candidates, incorporating the principles of Extreme Programming (XP) to elevate its development and deployment processes. In the dynamic realm of political campaigns, effective voter data management is pivotal for strategizing, targeting, and engaging with constituents. The application embraces XP methodologies to ensure rapid and adaptive development, fostering continuous feedback, collaboration, and responsiveness to evolving campaign dynamics. The XP approach is integrated into the software development life cycle, emphasizing practices such as pair programming, frequent releases, and continuous integration. This not only accelerates the application's time-to-market but also allows for seamless adjustments in response to emerging campaign needs. The iterative nature of XP enhances the adaptability of the Voter Data Management Application, ensuring that it remains aligned with the evolving requirements of legislative campaigns. Key functionalities of the application include efficient data entry for demographic details, voting history, and issue preferences, creating a centralized repository for streamlined access. Advanced analytics tools, developed and refined iteratively, provide dynamic insights into voter behavior, enabling candidates to tailor their messages and outreach strategies. The XP-driven development process also reinforces the application's security measures, ensuring robust protection of sensitive voter information and compliance with privacy regulations. The "Voter Data Management Application" not only serves as a powerful resource for legislative candidates but also displays the benefits of applying Extreme Programming methodologies to political technology. By combining efficient voter data management with agile and collaborative development practices, this application contributes to a more informed and engaged electorate, fostering a democratic process that is responsive to the needs of the constituents.